Development and Sustainability of National Food Composition Databases for use in Dietary Monitoring and Public Health Nutrition in the Eastern Mediterranean Region - Warthon-Medina, M. (2019)
Background:Similar to Western Countries, the Eastern Mediterranean Region (EMR) also presents major public health issues associated with the increased consumption of sugar, fat (saturated fatty acids, trans fatty acids), salt. Therefore, one of the policies of the World Health Organization’s (WHO) EMRO is to reduce the intake of these, to address the risk of obesity and non-communicable diseases such as diabetes, cardiovascular disease and cancer. In order to do this, access to updated, standardized, harmonized food composition data (FCD) is essential. Aims: Objectives within this Medical Research Council GCRF project, working jointly with WHO–EMRO, are to assess the status of national FCD and to provide training and capacity development in the use of improved standardized methodologies to update FCD as well as dietary intake methods, use of suitable biomarkers of nutritional value and to determine health outcomes in the low- and middle-income countries (LMIC) of this region. By identifying specific regional needs for FCD compilation, detailed training workshops can be developed to enable the production of vital high-quality harmonised data in the EMR including: Iran, Iraq, Pakistan, Kuwait, Tunisia, Morocco, Sudan, Egypt, Jordan together with Mauritania. This capacity building will lead to the development and sustainability of up-to-date national and regional FCD for use in dietary monitoring assessment in food and nutrient intakes. Methods: Training needs were identified, and short-term scientific missions organized for researchers via training, knowledge exchange workshops and short-term exchange of researchers. Training at CAPNUTRA (Serbia) and INNTA (Tunisia) included the use of improved standardized methodologies for food composition and food intake for 7 EMR countries leading to development of national FCD, enabling upload onto the EuroFIR data platform. A 3-week training course on analytical methods was carried out at INSA (Portugal) for analysts from Egypt, Jordan and Sudan. Key findings: A total of 45 participants from 13 countries including 10 EMR and 3 invited West African countries attended 5 workshops and training exchanges. Training topics included: value documentation and quality assessment; food composition data tools (Food Composition And System Environment (FoodCASE), Diet assess and Plan (DAP), Nutritics; food classification and description of composite dishes, recipe calculation approaches; use of yield and retention factors; EuroFIR e-learning tools and case studies; laboratory food analysis (vitamins A, B1, B2, C, D2, D3 and E, fatty acids, amino acids, minerals, fibre); quality management system; food metrology principles; validation of chromatographic methods; and food label legislation. 6 countries have imported their FCD, as open access, into the EuroFIR FoodEXplorer platform. The WHO-EMRO jointly with MRC GCRF project funded and mobilized research institutions in over 10 countries, with more focus on identifying traditional dishes and micronutrients. Conclusions and project Implications: The use of improved standardized methodologies for food composition and dietary intake will produce robust measurements that will reinforce dietary monitoring and policy in LMIC. The capacity building from this project has led to searchable national food composition data from developing/emerging countries being made available in an open access form for the first time. WHO-EMRO, is funding further updates of FCD tables in Jordan, Lebanon, Oman, Sudan, Tunisia, Morocco, Pakistan, Iran Egypt, and UAE, with the focus on identifying TFA, SFA, salt and sugar in addition to micronutrients.